Update Treatment of Male Androgenetic Alopecia - Damai Trilisnawati; Sarah Diba; Yuli Kurniawati; Suroso Adi Nugroho; Rusmawardiana Rusmawardiana; Raden Pamudji (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Male androgenetic alopecia (MAGA), also known as androgenetic alopecia, is the most common hair loss in males who have a genetic predisposition. The pattern of baldness in MAGA starts from the frontal area in a triangular pattern, followed by progressive thinning of the vertex until baldness occurs. Generally, the diagnosis of MAGA is established by clinical examination. FDA has approved a combination of topical minoxidil and oral finasteride for MAGA treatment. Currently, there is another treatment option like dutasteride, a prostaglandin analog, ketoconazole, and co-adjuvant therapy like laser therapy, hair transplantation, and so on. Purpose: To provide an updated treatment for MAGA. Review: Etiopathogenesis of MAGA is influenced by genetic susceptibility and hormonal factors. The European Consensus Group set the evaluation diagnosis of MAGA to include a historyof hair fall, physical examination, hair examination, supporting examination, and clinical documentation. There are therapeutic options for MAGA, including antiandrogen therapies, androgen-independent therapies, and co-adjuvant therapies. The FDA has approved a combination of topical minoxidil and oral finasteride for MAGA treatment. MAGA may affect patients’ quality of life and self-esteem. In general, patients expect higher. Conclusion: MAGA is the most common progressive hair loss in males. The MAGA therapy is expected to achieve cosmetically significant regrowth and to slow additional hair loss.